Volatility of Aprotic Ionic Liquids - A Review - José M. S. S. Esperança (2010)
Research on the volatility of aprotic ionic liquids is reviewed. This topic is limited to aprotic liquids since measurements have led to a generalization that this class of substances possesses extremely low vapor pressures. For research related to this topic, the period covered is 2003 to 2008. The review begins with a discussion of the earliest successful study of thermal vaporization of aprotic ionic liquids, the earliest indirect measurements of their vapor pressure, the first proof of conventional distillation of ionic liquids, and competition of vaporization with thermal decomposition seen at moderately high temperatures of (200 to 300) °C. The review then briefly discusses the nature of the vapor phase and proceeds to analyze the various approaches used to measure or predict the vapor-liquid equilibrium properties of ionic liquids, including their normal boiling point, vapor pressure, and enthalpy of vaporization. It is proposed that the most reliable thermodynamic data exist solely for the enthalpy of vaporization, and thus this property would be the best target for predictive approaches. Predictive approaches to calculate the enthalpy of vaporization are discussed in light of their ability to predict the experimentally observed trends with molar mass. The review concludes with a forward look at the following: expected effect of gas-phase ion clusters; anticipated trade-off between the energetic gain and the entropic penalty for cluster formation; and the possibility of a Trouton rule for the vaporization of ionic liquids.